Development of a Model for the Validation of Work Relative Value Units for the Medicare Physician Fee Schedule - Wynn, Barbara O. (RAND Corporation, 2015)
The Centers for Medicare & Medicaid Services (CMS) uses the resource-based relative value scale to pay physicians and other practitioners for their professional services. The relative values for physician work measure the relative levels of professional time, effort, skill, and stress associated with providing services. CMS asked RAND to develop a model to validate the physician work values using external data sources.